NCIA ACKNOWLEDGES USM EXPERTISE TO HELP DEVELOP THE NORTHERN REGION - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PUTRAJAYA, 24 June 2015 Universiti Sains Malaysia (USM) has moved beyond its activities in knowledge transfer and research after being recognised by the Northern Corridor Implementation Authority (NCIA) to work together in developing the northern states of Peninsular Malaysia.